Mycophenolate mofetil: safety and efficacy in the prophylaxis of acute kidney transplantation rejection - Pranav Dalal; Monica Grafals; Darshika Chhabra; Lorenzo Gallon (Dove Medical Press, 2009)
Pranav Dalal1, Monica Grafals2, Darshika Chhabra2, Lorenzo Gallon21Department of Medicine, Mount Sinai Hospital, Chicago, USA; 2Northwestern University–Feinberg School of Medicine, Chicago, USAAbstract: Mycophenolate mofetil (MMF), a prodrug of mycophenolic acid (MPA), is an inhibitor of inosine monophosphate dehydrogenase (IMPDH). It preferentially inhibits denovo pathway of guanosine nucleotide synthesis in T and B-lymphocytes and prevents their proliferation, thereby suppresses both cell mediated and humoral immune responses. Clinical trials in kidney transplant recipients have shown the efficacy of MMF in reducing the incidence and severity of acute rejection episodes. It also improves long term graft function as well as graft and patient survival in kidney transplant recipients. MMF is useful as a component of toxicity sparing regimens to reduce or avoid exposure of steroids or calcineurin inhibitor (CNI). Enteric-coated mycophenolate sodium (EC-MPS) can be used as an alternative immunosuppressive agent in kidney transplant recipients with efficacy and safety profile similar to MMF.Keywords: mycophenolate mofetil, kidney transplantation, acute rejection, toxicity sparing